1990
DOI: 10.1002/ssu.2980060604
|View full text |Cite
|
Sign up to set email alerts
|

Gynecologic tumor markers

Abstract: The advent of monoclonal technology has increased the potential utility of antibody-dependent tumor marker assays in gynecologic oncology. The availability of unlimited quantities of several pure monoclonal antibodies directed against novel epitopes on tumor-associated antigens has permitted development of highly sensitive assays for serum markers. Traditional assays for human chorionic gonadotropin (hCG), NB/70K and TA-4 have been improved. CA 125 has provided a useful first-generation marker for monitoring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Ovarian carcinoma-associated antigen 125 (CA 125), although of limited specificity, is the best marker for ovarian cancer to date and is able to detect over 80% of patients with advanced disease [5]. Ovarian carcinoma-associated antigen 125 (CA 125), although of limited specificity, is the best marker for ovarian cancer to date and is able to detect over 80% of patients with advanced disease [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian carcinoma-associated antigen 125 (CA 125), although of limited specificity, is the best marker for ovarian cancer to date and is able to detect over 80% of patients with advanced disease [5]. Ovarian carcinoma-associated antigen 125 (CA 125), although of limited specificity, is the best marker for ovarian cancer to date and is able to detect over 80% of patients with advanced disease [5].…”
Section: Discussionmentioning
confidence: 99%
“…Any potential tumour marker has to be evaluated in the context with other parameters available. Ovarian carcinoma-associated antigen 125 (CA 125), although of limited specificity, is the best marker for ovarian cancer to date and is able to detect over 80% of patients with advanced disease [5]. For other substances however, such as a-fetoprotein (AFP), carcinoembryonic antigen (CEA) [23] and squamouscell-cancer antigen (SCC) [24], clinical utility is less certain, and an equally promising marker for endometrial or cervical cancer has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there has been considerable interest in developing predictive markers to assess the risk of a relapse in advanced EOC patients. The most famous biomarker in EOC is CA-125, which has been used in both diagnosis of the disease and monitoring of treatment [4-6]. Recent evidence indicates that the nadir CA-125 level after completion of primary treatment was associated with prognosis [7-11].…”
Section: Introductionmentioning
confidence: 99%